Палеоетноботанічні дослідження 2008 р. - Пашкевич, Г.О. (Археологічні дослідження в Україні, 2009)
The paper presents the data of palaeobotanic research of the following monuments from the territory of Ukraine dated from the Early Neolithic to the Mediaeval periods: Baiv of the Early Neolithic Volyn-Lyublin culture, Ostrih of Malytska culture, Kolomyitsiv Yar of Trypillya culture, Dykyi Sad of Biloserska culture, Yosypivka ІІІ of Velbarska culture, and Kyiv of Ancient Rus period.